Advances in Computational Intelligence Applications in the Mining Industry - Ganguli, Rajive; Dessureault, Sean; Rogers, Pratt (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This book captures advancements in the applications of computational intelligence (artificial intelligence, machine learning, etc.) to problems in the mineral and mining industries. The papers present the state of the art in four broad categories: mine operations, mine planning, mine safety, and advances in the sciences, primarily in image processing applications. Authors in the book include both researchers and industry practitioners.